Efektivitas Motivasi Kerja Terhadap Tingkat Turnover Intention Pada PT. BPR Prima Nadi - Wati, Ni Nengah Tirta; Sutriani, Ida Ayu Nyoman; Wijaya, I Gede Bayu (Guna Sewaka, 2025)
The objective of this research is to examine the impact of work motivation effectiveness on turnover intention at PT BPR Prima Nadi. The main issue underlying this study is the high rate of turnover intention among employees, which is suspected to be related to suboptimal work motivation provided. The research method used is an associative quantitative approach, with a population of 105 people. The sample was determined using Slovin's formula and proportionate stratified random sampling technique, resulting in 51 respondents. Data analysis was conducted using SPSS version 25 software, with a series of statistical tests including validity, reliability, normality, multicollinearity, heteroscedasticity, t-test, and coefficient of determination. The findings indicate that, partially, work motivation has a significant effect on turnover intention; meaning, the higher the employees' work motivation, the lower their tendency to leave the company.